Beyond alterity : German encounters with modern East Asia - Shen, Qinna; Rosenstock, Martin (Spektrum (New York, N.Y.), 2014)
With the economic and political rise of East Asia in the second half of the twentieth century, many Western countries have re-evaluated their links to their Eastern counterparts. Thus, in recent years, Asian German Studies has emerged as a promising branch within interdisciplinary German Studies. This collection of essays examines German-language cultural production pertaining to modern China and Japan, and explicitly challenges orientalist notions by proposing a conception of East and West not as opposites, but as complementary elements of global culture, thereby urging a move beyond national paradigms in cultural studies. Essays focus on the mid-century German-Japanese alliance, Chinese-German Leftist collaborations, global capitalism, travel, identity, and cultural hybridity. The authors include historians and scholars of film and literature, and employ a wide array of approaches from postcolonial, globalization, media, and gender studies. The collection sheds new light on a complex and ambivalentset of international relationships, while also testifying to the potential of Asian German Studies.